Implications of Fines in Sharia Procurement in the Early Stages of the Contract - Agun Pradika (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2024)
The imposition of late payment penalties in Islamic pawnshops at the initial stage of the contract has sparked debate. This study examines the implications of such penalties on the principles of justice, customers, funders, and Islamic financial institutions. Literature study and fatwa review are the basis of the discussion. The results show that fines that are not agreed upon at the beginning of the contract have the potential to cause legal and sharia uncertainty, and open up opportunities for abuse of authority. The negative impact is a decrease in customer trust and tarnishing the reputation of Islamic financial institutions. The proposed solutions are the inclusion of a clear amount of fines in the contract, the involvement of the Sharia Supervisory Board, customer education, and the establishment of industry standards. The application of fair fines can be in the form of tiered fines, adjusted to the customer's ability, and accompanied by alternative fine options. Transparency and accountability of Islamic financial institutions are key to the sustainability of a fair and sharia-compliant Islamic pawnshop system.